(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
Maksud Sheikhzade’s numerous translations are noted for their high artistic quality. He introduced Uzbek readers to the masterpieces of more than fifty authors. Artistic translation plays a huge role in the development of culture and literature in our country and in the internationalization of social communist consciousness.